Social sustainability - Wollenberg, Eva Karoline; Colfer, C.J.P. (1997)
In discussing conservation issues and dilemmas it is common to hear the term 'social sustainability' or reference to the 'social aspects of sustainability'. Although these concepts are used frequently, they are rarely defined. The authors offer three definitions that can be used separately or in combination. Social sustainability can be defined as the maintenance of people's well-being (with a focus on the people most dependent on the resource), the actions of people to sustain the resource, or the maintenance of equitable benefits across generations. It is necessary to be clear about which definition is used to have a mutual understanding of what is to be achieved through social sustainability. The authors stress that any definition of sustainability is inherently relative and bound by the limits of the time, place and people being considered. In any situation, it is important to maintain flexibility in one's vision of what social sustainability is and be open to revising that view based on changing and or different circumstances.